Pengaruh Kombinasi Pijat BBLR dan KMC Terhadap Rooting-Sucking ReflexNeonatus BBLR Di RSUD Sleman Tahun 2016 - Wahyu Surya Rhomawati; Dwiana Estiwidani; Sujiyatini Sujiyatini (Poltekkes Kemenkes Yogyakarta, 2017)
Infant Mortality Rate (IMR) was one measure of the health status of a country. Various attempts were made to reduce IMR. One of theLBW problems was a weight that did not increase due rooting sucking reflex was not robust. This study was aimed determine thedifference rooting sucking reflex LBW infants neonatal who did a combination of massage and KMC compared to those who do onlyKMC in RSUD Sleman 2016. This type of study was the experiment. The study design was a non equivalent control group. Study wasconducted in RSUD Sleman on November 1 until Desember 30, 2016. The subjects were LBW neonates in hospitals who birthed onOctober to December 2016 that matched with criteria. The total sample in this study were 46 respondents. Data collected by formobservation of rooting sucking reflex and stopwatch. Analysis of data used Man Whiteney and Wilcoxon. Bivariable analysisresulted count value z> z table and a p-value <0.05. There was a significant difference between LBW who get massage combinationwith KMC compared only KMC. The conclusion from this study was there were different effect LBW message combination with KMCand KMC to rooting sucking reflex neonatal LBW in RSUD Sleman 2016.